A Combined Metagenomics and Metatranscriptomics Approach to Unravel Costa Rican Cocoa Box Fermentation Processes Reveals Yet Unreported Microbial Species and Functionalities - Verce, Marko; Schoonejans, Jorn; Hernandez Aguirre, Carlos; Molina-Bravo, Ramón; De Vuyst, Luc; Weckx, Stefan (Frontiers in Microbiology, 2021)
Cocoa fermentation is the first step in the post-harvest processing chain of cocoa and is important for the removal of the cocoa pulp surrounding the beans and the development of flavour and colour precursors. In the present study, metagenomic and metatranscriptomic sequencing were applied to Costa Rican cocoa fermentation processes to unravel the microbial diversity and assess the function and transcription of their genes, thereby increasing the knowledge of this spontaneous fermentation process. Among 97 genera found in these fermentation processes, the major ones were Acetobacter, Komagataeibacter, Limosilactobacillus, Liquorilactobacillus, Lactiplantibacillus, Leuconostoc, Paucilactobacillus, Hanseniaspora, and Saccharomyces. The most prominent species were Limosilactobacillus fermentum, Liquorilactobacillus cacaonum, and Lactiplantibacillus plantarum among the LAB, Acetobacter pasteurianus and Acetobacter ghanensis among the AAB, and Hanseniaspora opuntiae and Saccharomyces cerevisiae among the yeasts. Consumption of glucose, fructose, and citric acid, and the production of ethanol, lactic acid, acetic acid, and mannitol were linked to the major species through metagenomic binning and the application of metatranscriptomic sequencing. By using this approach, it was also found that Lacp. plantarum consumed mannitol and oxidized lactic acid, that A. pasteurianus degraded oxalate, and that species such as Cellvibrio sp., Pectobacterium spp., and Paucilactobacillus vaccinostercus could contribute to pectin degradation. The data generated and results presented in this study could enhance the ability to select and develop appropriate starter cultures to steer the cocoa fermentation process toward a desired course.